Beleza sustentável: desvendando a motivação de consumo consciente de cosméticos verdes - Silva , Keloane Mendes da (2024)
The main objective in this research was to investigate the effect of trust and environmental motivations (intrinsic and extrinsic) on the conscious consumption of green cosmetics regarding social and ecological dimensions. The consumption of so called green cosmetics is growing exponentially, not only in Brazil, but throughout the world, with skin care products dominating this market. We chose to base this research on Self-Determination Theory, filling a gap in the studies on cosmetic consumption behavior. We conducted a survey with 386 consumers of green skin cosmetics. The results reveal that trust plays a crucial role as an influential precursor in the formation of both intrinsic and extrinsic motivations, the latter being formed by the dimensions of external regulation and introjected regulation. Furthermore, the results highlight the significant impact of intrinsic and extrinsic motivations on conscious consumption behavior, especially in the environmental context, where consumer trust plays a more important role in contributing to preference for products with environmental attributes when compared to social themes. These results serve as important insights for marketing managers and the industry itself in developing marketing strategies, especially in defining product attributes that will attract more attention from conscious consumers.